The structure of schooling : [edited by] readings in the sociology of education - Beattie, Irenee R.; Arum, Richard, 1963-; Ford, Karly (Sage Publications, 2015)
Examines important topics and exposes students to examples of sociological research on schools. Drawing from classic and contemporary scholarship, this book helps you examine issues and reflect diverse theoretical approaches to studying the effects of schooling on individuals and society.